Meltdown the neuroscience of stress - Eggers, Arnold (Cambridge Scholars Publishing, 2019)
This book investigates the concept of stress, how it causes a cluster of life-threatening diseases, and what you can do to save yourself. It is a summation of what the author, a neurologist, has learned about stress throughout his career. Stress damages the brain in specific ways that cause migraine headaches, high blood pressure, and obesity. These conditions lead eventually to stroke, Alzheimer's disease, atherosclerosis, and heart attacks. It all starts in the brain. The book will appeal to the medical community, such as doctors, nurses and medical students, as well as the general reader wh.